2016
DOI: 10.1021/acscatal.6b00911
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Key Role of Phosphine−Sulfonate Ligands in Palladium-Catalyzed Ethylene Polymerization: Effect of Ligand Structure on the Molecular Weight and Linearity of Polyethylene

Abstract: The mechanism of linear polyethylene formation catalyzed by palladium/phosphine−sulfonate and the effect of the ligand structure on the catalytic performance, such as linearity and molecular weight of the polyethylene, were reinvestigated theoretically and experimentally. We used dispersion-corrected density functional theory (DFT-D3) to study the entire mechanism of polyethylene formation from (R 2 PC 6 H 4 SO 3 )PdMe(2,6-lutidine) (R = Me, t-Bu) and elucidated the key steps that determine the molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 88 publications
(72 reference statements)
9
81
0
Order By: Relevance
“…[26] Olefin polymerization involving these catalysts produce much more linear polymers than their Brookhart counterparts,a st he combination of as trong and sterically bulky s donor and aw eak s donor promote linear polyethylene formation. [27] Copolymerization of ethylene and polar vinyl monomers with these catalysts has been investigated, [28] and polymers with up to 7% polar monomer incorporation within the main polymer chain, not exclusively at the end, are obtained. [29] Recent advances have investigated nickel catalysts containing phosphine-sulfonate ligands with varied sterics, [30] electronics, [31] and ligand substituents [32] which have afforded catalysts with higher olefin polymerization rates compared to their palladium counterparts with similar levels of polar monomer incorporation.…”
Section: Late-transition and Rare-earth Metal Catalysismentioning
confidence: 99%
“…[26] Olefin polymerization involving these catalysts produce much more linear polymers than their Brookhart counterparts,a st he combination of as trong and sterically bulky s donor and aw eak s donor promote linear polyethylene formation. [27] Copolymerization of ethylene and polar vinyl monomers with these catalysts has been investigated, [28] and polymers with up to 7% polar monomer incorporation within the main polymer chain, not exclusively at the end, are obtained. [29] Recent advances have investigated nickel catalysts containing phosphine-sulfonate ligands with varied sterics, [30] electronics, [31] and ligand substituents [32] which have afforded catalysts with higher olefin polymerization rates compared to their palladium counterparts with similar levels of polar monomer incorporation.…”
Section: Late-transition and Rare-earth Metal Catalysismentioning
confidence: 99%
“…Ligands do have critical influences on the ethylene polymerization process, thus greatly influencing the microstructures of the resulting polymers . Ligands such as α‐diimines,[4f], , [15b], , , phosphine‐sulfonates,, [15a], salicylaldimines,, , [15d], [19a], and iminopyridines, forming five‐ or six‐membered chelate rings with the metal center are still common for catalyst design because of their higher stability, and modification of ligands in substituents and backbone is a common – but not easy – way to design new, high‐performance catalysts. In fact, there are still some examples of failed attempts to design catalysts with special performances, as can be seen from recent reports …”
Section: Ni and Pd Catalysts And Their Effectsmentioning
confidence: 99%
“…Electronic effects mainly originate from the electron‐donating or electron‐withdrawing natures of substituents whereas steric effects are related to interatomic distances and angles, the sizes of substituents, the ionic radii of the transition metals, and so on. [15c] Usually, bulky substituents near the metal can block the axial site of the metal center, thus suppressing chain transfer[19b], , [27l] and affording polymers with higher molecular weights . Electronic perturbation of ligands can modify the net charge at the metal center, to yield polymers with a variety of microstructures (including changing the insertion locations of polar comonomers for copolymers) and can markedly influence the activities of ethylene polymerization.…”
Section: Ni and Pd Catalysts And Their Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphine sulfonate ligands combine the strong σ‐donating phosphine and weak σ‐donating sulfonate groups. This electron‐unsymmetric feature was generally believed to be able to inhibit β‐H (X) elimination, enabling the formation of linear polymers and ethylene‐polar monomer copolymers . However, Jordan group and Nozaki group showed that the change of the phosphine group to a stronger σ‐donating carbene group led to inactive palladium catalysts (Scheme , II and III ) ,.…”
Section: Introductionmentioning
confidence: 99%